ANALYSIS OF MACHINE LEARNING METHODS FOR DETECTING MALICIOUS PROCESSES IN A CORPORATE NETWORK - Samoilenko, Vladyslav; Gakhov, Sergii (Collection of scientific papers «ΛΌГOΣ», 2025)
In the modern digital environment, cybersecurity has become critically important for corporate networks. According to NETSCOUT, approximately 7.9 million DDoS attacks were recorded in the first half of 2023, which is 31% more than in the previous year [4]. In Ukraine, the situation has also worsened: according to the State Service of Special Communications and Information Protection, the number of cyberattacks increased by 62.5% in 2023, reaching 1,105 incidents [2]. Although most attacks were aimed at government institutions, corporate networks have also been significantly affected.